2022
DOI: 10.3389/fonc.2022.994672
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine metabolism in cancers: Targeting the oxidative homeostasis

Abstract: Glutamine is the most abundant amino acid in blood and tissues, and the most important nutrient except for glucose in cancer cells. Over the past years, most studies have focused on the role of Gln metabolism in supporting energy metabolism rather than maintaining oxidative homeostasis. In fact, Gln is an important factor in maintaining oxidative homeostasis of cancer cells, especially in “Glutamine addicted” cancer cells. Here, this paper will review the recent scientific literature about the link between Gln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 127 publications
0
9
0
Order By: Relevance
“…Competition for glutamine uptake also exists between tumor cells and immune cells in the TME. Studies have demonstrated that competitive consumption of glutamine by tumor cells could lead to suppressed antitumor immune response in many cancers [ 138 , 139 ]. Inhibiting glutamine uptake in tumor cells could potentially enhance glucose uptake, indicating that glutamine may serve as the limiting factor in the TME [ 140 ].…”
Section: Components Of the Npc Tumor Microenvironmentmentioning
confidence: 99%
“…Competition for glutamine uptake also exists between tumor cells and immune cells in the TME. Studies have demonstrated that competitive consumption of glutamine by tumor cells could lead to suppressed antitumor immune response in many cancers [ 138 , 139 ]. Inhibiting glutamine uptake in tumor cells could potentially enhance glucose uptake, indicating that glutamine may serve as the limiting factor in the TME [ 140 ].…”
Section: Components Of the Npc Tumor Microenvironmentmentioning
confidence: 99%
“…A raised glutamine metabolism also quenches ROS to compromise oxidative stress by replenishing the mitochondrial NADPH pool through glutathione generation (Gong et al, 2022 ). Indeed, glutamine can facilitate a stem cell phenotype by maintaining the redox status (Liao et al, 2017 ).…”
Section: Metabolic Reprogramming Shapes Tumorigenesismentioning
confidence: 99%
“…In the 1950s, the American physiologist Harry Eagle was the first to propose that proliferating cancer cells exhibit an increased requirement for Gln based on the observation that human carcinoma cells (HeLA strain) exhibit higher uptake of Gln than other amino acids 276 . Gln, the most abundant nonessential amino acid in the plasma and tissues, is the most indispensable nutrient besides glucose for cancer metabolism in various cancer types, including pancreatic ductal adenocarcinoma (PDAC), AML, colon cancer, PCa, kidney cancer, lung cancer, liver cancer, and glioma 277–279 . On the one hand, amino acids are metabolized to meet the increased requirements for protein synthesis in proliferating cancer cells.…”
Section: Rna Methylation and Cancer Metabolismmentioning
confidence: 99%
“… 276 Gln, the most abundant nonessential amino acid in the plasma and tissues, is the most indispensable nutrient besides glucose for cancer metabolism in various cancer types, including pancreatic ductal adenocarcinoma (PDAC), AML, colon cancer, PCa, kidney cancer, lung cancer, liver cancer, and glioma. 277 , 278 , 279 On the one hand, amino acids are metabolized to meet the increased requirements for protein synthesis in proliferating cancer cells. On the other hand, the requirement for the catabolism of amino acids, especially Gln, for energy generation and biomass synthesis surpasses that for protein synthesis in cancer cells.…”
Section: Rna Methylation and Cancer Metabolismmentioning
confidence: 99%